A Speck in the Brother’s (Sister’s) Eye?: An Ethical Analysis of Church Discipline as Practiced in the Evangelical Lutheran Church in Tanzania (ELCT) - Moshi, Nehemia Godwin (Africa theological journal /published by the Faculty of Theology, Tumaini University Makumira, 2024)
Being motivated by the enduring practice of church discipline in the ELCT, albeit critique, this article analyses some aspects of church discipline from an ethical stand point. The article is informed by a descriptive analysis of previous research on church discipline in the ELCT. Scrutiny of parts related to church discipline in the ELCT hymnal - Tumwabudu Mungu Wetu, the church constitutions, and some interviews were carried out. The analysis shows that church discipline as practiced in the ELCT is imbued with flaws among which are failure to address issues contextually, gender bias and contradiction with the ELCT liturgy, especially concerning absolution and benediction. Such flaws mask and even contradict with the Lutheran identity as reflected in tenets of justification by grace, priesthood of believers and freedom. The study reveals that the enduring practice of church discipline in the ELCT is attributed to the need of differentiating and correcting wrong doings in various contexts. From this perspective, church discipline is considered ethical as to its intention. However, the bias and contradictions manifest in the practice of church discipline, render church discipline as practiced in the ELCT unethical. It is recommended that the ELCT could review the practice in efforts to align it with the mission of the church and the fast-changing context.